Development and Psychometric Properties of Self-Harm Intention Scale in Indonesian Students - Putri, Audrey Nabila Firmansyah; Fitriani, Arifia; Ferissa, Rahma Shafa; Rahmawati, Putri; Ziaulhaq, Jihan; Sari, Novita (Jurnal Paedagogy, 2026)
This study aims to develop and evaluate the validity and reliability of the Self-Harm Intention Scale based on Ajzen’s Theory of Planned Behavior, comprising two components: attitude toward the behavior and subjective norm. A quantitative approach was employed involving 206 school and university students in Bandung, with data collected through an online survey. Item analysis using item–rest correlation identified five items with discrimination indices below 0.30, while the remaining items demonstrated acceptable discriminatory power. Content validity, assessed using Aiken’s V, yielded a value of 1.00 for 27 items, indicating excellent agreement among experts. Confirmatory Factor Analysis (CFA) indicated an adequate model fit, and the scale demonstrated very high internal consistency, with reliability coefficients ranging from 0.962 to 0.978. Overall, the findings suggest that the scale has strong potential as an early screening tool for self-harm intention. These results underscore the importance of educational settings in identifying early signs of self-harm intention and suggest that schools and higher education institutions can play a more active role in early detection and prevention when supported by a valid and reliable measurement instrument. Future studies are recommended to examine the external validity of the scale and to involve more diverse samples.